A study of 8,300-year-old Jomon human remains in Japan using complete mitogenome sequences obtained by next-generation sequencing - Fuzuki Mizuno; Yasuhiro Taniguchi; Osamu Kondo; Michiko Hayashi; Kunihiko Kurosaki; Shintaroh Ueda (Taylor & Francis Group, 2020)
Ancient human remains have been assigned to their mitochondrial DNA (mtDNA) haplogroups. To obtain efficiently deep and reliable nucleotide sequences of ancient DNA of interest, we achieved target enrichment followed by next-generation sequencing (NGS). Complete mitochondrial genome (mitogenome) sequences were obtained for three human remains from the Iyai rock-shelter site of the Initial Jomon Period in Japan. All the Jomon mitogenomes belong to haplogroup N9b, but no sequences among them were identical. High genetic diversity was clarified even among the Jomon human remains belonging to haplogroup N9b, which has been described as a haplogroup representing the Jomon people.